Enhancing milk quality in Uganda: Challenges and innovations in the dairy value chain - Ariong, Richard M.; Van Campenhout, Bjorn; Kariuki, Sarah W.; Chamberlin, Jordan (International Food Policy Research Institute, 2024)
Over the past few decades, Uganda’s dairy sector has transformed from mostly subsistence activities into a dynamic and modern industry—a shift enabled by government initiatives, private sector investments, and the introduction of better technologies and practices. But the industry still faces challenges, particularly in establishing a market for high-quality milk.